(untitled) (Asian Journal of Pharmaceutical and Health Sciences, 2018)
Sacral plexus nerve block provides post-operative pain relief after below knee surgery and knee surgery. Many studies with different approaches for sacral plexus nerve block have been conducted to demonstrate the efficacy of it. The findings are conflicting. Hence, an attempt was made in the present research to study the efficacy of peripheral nerve stimulator guided sacral plexus block for post-operative pain management in below knee orthopaedic surgery. Sixty patients aged 18 to 60 years scheduled for unilateral below knee orthopaedic surgery under spinal anaesthesia were included. Sacral plexus nerve block was given by posterior approach before spinal anaesthesia using 0.5 % bupivacaine. Pain was assessed using visual analogue scale (VAS) score. Diclofenac sodium 75 mg intra-venous was given slowly as rescue analgesia when VAS score was > 4. Time of supplemental analgesia was noted. Primary outcome measures were to study duration of sacral plexus block and the requirement of rescue analgesia whereas secondary outcome measures were to study the adverse effects of sacral plexus block. Single shot sacral plexus block provided effective pain relief up to 24 hours in below knee orthopedic surgery. It decreased analgesic drugs consumption significantly post-operatively. No adverse systemic toxicity was observed within 24 hours after the operation. Single shot sacral plexus nerve block provided effective pain relief to majority of the patients up to 24 hours in below knee orthopaedic surgery and decreased analgesic drugs requirement postoperatively. Sacral plexus nerve block is safe with no adverse effects.